2010
DOI: 10.1111/j.1471-0528.2009.02473.x
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship of complement‐activation fragments and angiogenesis‐related factors in early pregnancy and their association with pre‐eclampsia

Abstract: Objective To determine the interrelationships during early pregnancy of complement-activation fragments Bb, C3a and sC5b-9, and angiogenesis-related factors placental growth factor (PiGF), soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng), and their associations with pre-eclampsia. Design Prospective cohort study. Setting Denver complement study (June 2005–June 2008). Population A total of 668 pregnant women with singleton gestations, recruited between 10 and 15 weeks of gestation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 43 publications
1
56
2
Order By: Relevance
“…There was no correlation between local expression and plasma level for CCL18 (r=-0.15; p=0.47) or CXCL10 (r=-0.22; p=0.23). For CCL22 we did not find any placental expression in the third trimester 117 and CCL20 was not detectable in the majority of the plasma samples. Correlation tests were therefore not performed for these chemokines.…”
Section: Plasma Levels Of Chemokinescontrasting
confidence: 66%
“…There was no correlation between local expression and plasma level for CCL18 (r=-0.15; p=0.47) or CXCL10 (r=-0.22; p=0.23). For CCL22 we did not find any placental expression in the third trimester 117 and CCL20 was not detectable in the majority of the plasma samples. Correlation tests were therefore not performed for these chemokines.…”
Section: Plasma Levels Of Chemokinescontrasting
confidence: 66%
“…In particular, obesity in conjunction with elevated Bb levels increases the risk of PE beyond elevated Bb alone. 21 This information may further elucidate specific groups of women at risk of severe preeclampsia related to abnormal alternative complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…While not all related studies have been conclusive, both the classical and the alternative CS pathway have been recognized in the pathogenesis of PE. 10,37,38 Bb fragments may represent a sign of the exaggerated alternative CS pathway activation occurring in the early severe PE. 38 Clinical studies reported that CS is activated with increased terminal complex (C5b9) formation in the third trimester of normal human pregnancy, and further in PE.…”
Section: Complement Systemmentioning
confidence: 97%
“…49 Alterations in circulating sFlt-1 and placental growth factor (PlGF) appear to be involved in the pathogenesis of PE. 37 Authors identified elevated expression of sFlt-1 by gene expression profiling in placentas delivered from women with PE. 50 Moreover, several sFlt-1 variant isoforms have been identified and shown to be upregulated in PE.…”
Section: Endothelial Cell Functionmentioning
confidence: 98%